Simulasi Sistem Monitoring Kebun Pintar Berbasis IoT dengan Cisco Packet Tracer - Marhaeni, Ni Kadek Dwi; Muliantara, Agus (Jurnal Nasional Teknologi Informasi dan Aplikasnya; Vol 3 No 3 (2025): JNATIA Vol. 3, No. 3, Mei 2025DO - 10.24843/JNATIA.2025.v03.i03.p02, 2025)
The agricultural sector faces the ongoing challenge of enhancing productivity while ensuring sustainability. Inspired by previous research on automatic irrigation sensors, the concept of a smart garden has emerged as a promising solution. This study extendsprior work by developing and implementing four distinct sensors: temperature, automatic watering, air humidity, and motion sensors. Leveraging machine-to-machine communication, these sensors integrate into an environmental monitoring system to optimize resource utilization and maintain ideal plant conditions. By utilizing Cisco Packet Tracer software, this research simulates a comprehensive smart garden system, offering insights into monitoring garden environments and automating agricultural processes. With a focus on data-driven decision-making, this study contributes to a smarter, more sustainable agricultural vision.